Pengaruh Manfaat, Kemudahan Penggunaan, Privasi Dan Peningkatan Kinerja Seseorang Terhadap Pengadopsian Cloud Computing Pada UMKM - Paulina Rante; Elsa Imelda (CV. Ulil Albab Corp, 2024)
This study was conducted to determine whether the factors of benefits, ease of use, privacy, and improving one's performance can significantly influence the adoption of cloud computing among MSME players. The population of this study were MSME players in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas in 2024. The sample selection was carried out using a non-probability sampling technique, namely convenience sampling with the snowball method. This research is quantitative research conducted by distributing questionnaires to 110 respondents as entrepreneurs or workers of Jabodetabek MSMEs. Based on the results of this study, it can be found that the perceived ease-of-use factor has a significant influence on the adoption of clous computing among MSME players. However, the perceived usefulness, privacy, and performance expectancy factors do not have a significant influence on the adoption of cloud computing among Jabodetabek MSMEs. The results of this study are expected to provide knowledge regarding what factors influence the adoption of cloud computing to increase attention, especially for MSME.